Back Cover: A Mycoplasma Genomic DNA Probe using Gated Nanoporous Anodic Alumina (ChemPlusChem 3/2017). Issue 3 (10th February 2017) - Pla, Luís; Xifré‐Pérez, Elisabet; Ribes, Àngela; Aznar, Elena; Marcos, M. Dolores; Marsal, Lluís F.; Martínez‐Máñez, Ramón; Sancenón, Félix
Abstract : The cover picture shows a nanoporous sensor loaded with rhodamine dye molecules (in blue) and functionalized with capping "molecular gates". In the absence of the bacterium Mycoplasma (in pink) the capped and loaded support shows negligible cargo release, while in the presence of the bacterium, specifically its DNA, the gates are opened and the fluorescent dye molecules are released. Details are given in the Communication by R. Martínez‐Máñez and F. Sancenón et al. onpage 337 in Issue 3, 2017 (DOI:10.1002/cplu.201600651 ).